Natural Language and Gettering of Information - Aleksandra KUZIOR; Katarzyna POSTRZEDNIK-LOTKO (Communications of International Proceedings, 2020)
The purpose of this article is to present the issues related to obtaining the information from available databases, to provide a definition of natural language (NL) and to identify the main tasks and challenges of NL processing (NLP), based on the available literature of artificial intelligence (AI). The following part of the article presents a short history of NLP, also points to existing basic methods by NL generation (NLG) systems and problems of the NL understanding system. Then, the methods of visualization and data mining techniques were indicated, and the summary gave the areas of application (including machine translation).
Keywords: Natural Language; Artificial Intelligence; Cognitive Science; Data Mining